HUBUNGAN ANTARA STRES DAN TINGKAT SOSIAL EKONOMI TERHADAP HIPERTENSI PADA LANSIA - Anita Dwi Windarsih; Suyamto; Aan Devianto (Jurnal Keperawatan Notokusumo, 2017)
Background:Stress is a universal phenomenon that occurs in everyday life and is inevitable and will be experienced by each person. The influence of stress can cause physical illness due to the weak and low body durability such as hypertension. The number of sufferers of hypertension rise and increasingly worrisome. Objective: Knowing relation between stress and socioeconomic level with hypertension on elderly. Method: The type of research was an analytical survey using descriptive correlation method. There were 71 people as the samples. To collect data the writer used questionnaires while to analyze data the writer used techniques of statistic with univariate analysis. Result: The data analysis showed that: (1) statistical test showed that the value of correlation coefficient (r) was negative (-0,259) which meant that the higher socioeconomic level caused the lower case of hypertension while ? value of 0,259 meant that there was a meaningful relation between stress in elderly with hypertension but the relation belonged to low. (2) statistical test showed that the value of correlation coefficient (r) was positive (0,390) which meant that the higher stress in elderly cause the higher case of hypertension, while ? value of 0,001 meant that there was a meaningful relation between stress in elderly with hypertension but the relation belonged to low. Conclusion: There was relation between stress and socioeconomic level with hypertension on elderly in the hamlet of Bibis Krambil Sawit Saptosari Gunung Kidul with R of 0,501.